Relationship between Mental Rumination and Academic Burnout among Medical Students of Mazandaran University of Medical Sciences - maryam hasannezhad reskati; seyyed hamze hoseini; Misagh Shafizad; Farkhondeh Ahmadabadi (Mazandaran University of Medical Sciences, 2019)
Introduction and purpose: There exist several factors affecting the academic performance of students some of which improve academic performance, whereas some factors exert adverse effects on education. Therefore, the present study aimed to determine the relationship between obsessive-compulsive disorder and academic burnout among students of Mazandaran University of Medical Sciences. Methods: The statistical population of this descriptive-analytical study included general medical students out of whom 285 students were selected as the research population by simple random sampling. Data collection instruments included Nolen-Hoeksema and Morrow Mental rumination questionnaire and Breso›s academic burnout questionnaire. Subsequently, the data were analyzed using the correlation method. Results: Based on the results of the current study, a positive and significant relationship was reported between rumination and burnout in both groups of girls and boys. The correlation coefficient between rumination and burnout in girls was measured at (r=0/335; sig=0/000) and (r=0/250; sig=0/012), respectively. Furthermore, this study revealed that rumination (F=3.339) and academic years (F=3/683) were found to be influential factors affecting academic burnout. However, the effect of rumination on academic burnout in terms of the academic year was not significant. Conclusion: The results indicated a positive and significant relationship between obsessive-compulsive disorder and academic burnout. Excessive stress, as well as long working hours and years of study, predisposes medical students to obsessive-compulsive disorder and in turn to academic burnout.